2015
DOI: 10.1590/s1806-92902015000300001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different feed restriction regimens on lamb performance and carcass traits

Abstract: -Fifty Najdi ram lambs weighing an average of 38.1±0.5 kg were utilized in this study to determine the effects of feed restriction level with or without subsequent realimentation on lamb performance and carcass composition. Lambs were allotted randomly and equally into five groups. The groups were fed a control diet ad libitum; two groups fed 0.90 and 0.80 of ad libitum intake throughout the eight-week period of the trial (R), and two groups fed 0.90 and 0.80 of ad libitum intake for a six-week period followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Compensatory growth is a complex metabolic function; it may be influenced by genetic factors, the age of animals, severity and duration of restriction, diet quality, and duration of the realimentation (3). There are conflict results about feed consumption during the realimentation phase; some studies reported a significant increase in feed intake (4,5) while others found no significant differences (1,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Compensatory growth is a complex metabolic function; it may be influenced by genetic factors, the age of animals, severity and duration of restriction, diet quality, and duration of the realimentation (3). There are conflict results about feed consumption during the realimentation phase; some studies reported a significant increase in feed intake (4,5) while others found no significant differences (1,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The decreases in ADG and FE and, consequently, in final body weight were commonly reported in several studies (Homem Júnior et al 2007Abouheif et al 2013Abouheif et al , 2015, being related that negative impacts are directly related to the nutritional plan imposed, resulting in an inadequate intake of nutrients (Cui et al 2018), in which are necessary to sustain the rapid growth and development of animal. When feed intake is insufficient to cover their maintenance requirements, animals make use of body reserves, causing weight loss, and the magnitude of the reserve mobilization will depend on the severity and duration of the feed shortage (Pastén et al 2010).…”
Section: Discussionmentioning
confidence: 89%
“…The compensatory gain cannot be attributed to DMI, since there was no difference between the restricted and ad libitum groups in both weight groups, but possibly due to the better feed efficiency of the feed restricted lambs (Yambayamba et al 1996;Abouheif et al 2015;Ma et al 2017). These results are in agreement with those of Abouheif et al (2013) andHomem Júnior et al (2010), but different from those found by Greeff et al (1986) andHomem Júnior et al (2007), who reported that the rapid gain during refeeding was associated with increased feed intake, which did not occur in the present study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations